Can a carbon permit system reduce Spanish unemployment? - Taran Fæhn; Antonio G. Gómez-Plana; Snorre Kverndokk (University of Oslo, Department of Economics, 2004)
This paper analyses whether recycling revenues from carbon emission permit auctions can reduce unemployment in the Spanish economy. Spain's deviation from EU's intermediate emission goals is more serious than for most other EU countries, and the unemployment is also well above the EU average. We use a CGE model that includes a matching model with two types of labour, and which allows for different pricing rules and returns-to-scale assumptions. We find that abatement reduces unemployment due to beneficial impacts of recycling the revenue from permit sales. Unemployment is more effectively abated when revenues are used to reduce labour taxes rather than indirect taxes. Contrary to other studies of Europe, we find that the best option is to reduce payroll taxes on skilled labour. This reform is the most successful both in increasing demand and in dampening the supply response to rising wages. All the recycling schemes also generate dividends in terms of welfare, but none offset the abatement costs entirely.
Keywords: D58; J68; Q38; 330; Spanish unemployment; Tax reform; Emission Permit Auctions; Employment dividend; Matching functions; Increasing returns to scale; Computable general equilibrium models; Arbeitslosigkeit; Emissionsrechte; Öffentliche Einnahmen; Steuerreform; Indirekte Steuer; Beschäftigungseffekt; Spanien; Emissionshandel; CGE-Modelling